The Influence of Fear of Missing Out (FoMO), Brand Image, and Influencer Marketing on the Purchase Decision of Glad2Glow Skincare Products - Nur Addina Haula Wibowo; Shenda Aprilia Christanti; Ardy Tri Yunianto (CV. Publikasi Indonesia, 2026)
The purpose of this study was to examine how digital marketing, influencer marketing, and fear of missing out affected customers' decisions to buy Glad2Glow skincare products, especially those who live in East Jakarta. This study employed a quantitative approach using an associative-causal methodology. A targeted sample selection was used to distribute questionnaires to 100 respondents in order to collect data. Using SPSS ver25 software, multiple linear regression was used to analyze the data. The study's findings demonstrate that digital marketing, influencer marketing, and fear of missing out all have a favorable and substantial impact on the choice to buy. In certain instances, though, the individual factors also appear to have a big impact on the decision to buy. In conclusion, digital marketing, influencer marketing, and Fear of Missing Out play important roles in shaping consumers’ purchasing decisions for Glad2Glow skincare products. Therefore, companies are encouraged to strengthen digital marketing strategies, collaborate with credible influencers, and design promotional activities that are able to attract consumer attention in a highly competitive skincare market.